Barriers and enablers to the implementation of healthy lifestyle interventions for people with disability living in supported accommodation: A systematic review using the consolidated framework for implementation research. Issue 2 (April 2023) - Hatzikiriakidis, Kostas; Ayton, Darshini; O'Connor, Amanda; Callaway, Libby; Carmody, Sarah; Skouteris, Helen; Green, Rachael
Abstract: Background: People with disability living in supported accommodation often experience significant health disparities, despite the availability of additional support. Healthy lifestyle interventions have been identified as one key health promotion strategy. Implementation science offers an opportunity to explore the factors that influence the efficacy and sustainability of these interventions, yet its application in this context has been underutilized. Objective: This systematic review synthesized the barriers and enablers to the implementation of healthy lifestyle interventions delivered to people with disability living in supported accommodation settings. Methods: A systematic review was conducted following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A search for relevant literature published between January 2011 and November 2021 was conducted across six databases. The findings of included studies were coded and analyzed according to the domains and constructs of the Consolidated Framework for Implementation Research (CFIR) via deductive content analysis. Results: Five studies were included, and their findings were mapped to 21 out of 38 constructs under the CFIR. Interventions from each study delivered health promotion education and training to staff and/or people with disability. The most prominent determinants that influenced implementation success included an intervention's relevance and its flexibility to adapt to the needs of people with disability, alongside organizational resourcing, and stakeholder endorsement in supporting implementation. Conclusions: The CFIR provided a systematic approach to explore the implementation of healthy lifestyle interventions. However, further research that is grounded in and guided by implementation science theories is warranted. Despite the scarcity of literature, several compelling, yet preliminary recommendations were drawn from the findings.